Annual Population Dynamics and Their Influencing Factors for an Endangered Submerged Macrophyte (Ottelia cordata) - Shen, Yichun; Lei, Jinrui; Song, Xiqiang; Ren, Mingxun (Frontiers in Ecology and Evolution, 2021)
Due to wetland loss, Ottelia cordata (O. cordata, Wallich) Dandy has been categorized as an endangered species on the List of Key Protected Wild Plants in China. Quantifying the relative importance of demographic (i.e., growth, survival, and reproduction) and habitat preference traits on the population dynamics (abundance) of O. cordata could guide how to develop the best recovery strategies of O. cordata, yet currently, there are no studies that investigate this. By monitoring monthly changes in O. cordata abundance and demographic traits (plant height, leaf area, flower sex ratio, and seed number) that were highly correlated with growth rate, photosynthetic rate, and water depth, we identified several relationships. Linear mixed-effect models and variance partition quantified the specific effects of four demographic traits and water depth on O. cordata abundance in three habitat types (paddyfield, stream, and spring). The linear mixed-effect models indicate that among the four demographic traits, height could be significantly positively correlated to abundance in all three habitat types. In contrast, other three traits (leaf area, sex ratio, and seed numbers) were non-significantly associated with abundance across each habitat. Height was determined by water depth, so water depth rather than photosynthetic rate and reproduction rate may promote the development and recovery of O. cordata populations. Variance partition results showed that water depth mediated the positive influence of growth rate on the abundance of O. cordata in the living habitats (paddyfield and spring). In contrast, water depth but not growth rate determined the abundance of O. cordata in the living habitat (stream). However, water depth had a significantly negative impact on the abundance of O. cordata in stream habitats, likely because all of the streams were shallow. Altogether, in the short term for avoiding the potential harm or even extinction of O. cordata, keeping appropriate water depth or transplanting O. cordata to spring should be an effective strategy because the water is not only deep enough but also clear in spring habitats. Additionally, water turbidity was shown to affect the density of O. cordata growth, wherein O. cordata was sparsely distributed when turbidity was high. Therefore, in the long run, to make the population gradually recovery, it will be necessary to restore the degraded wetland. This could be accomplished by reducing water pollution and removing sludge to reduce turbidity and increase hydrological connectivity.